Floor systems and the Friedman rule: The fiscal arithmetic of open market operations - Todd Keister; Antoine Martin; James McAndrews (Federal Reserve Bank of New York, 2015)
In a floor system of monetary policy implementation, the central bank remunerates bank reserves at or near the market rate of interest. Some observers have expressed concern that operating such a system will have adverse fiscal consequences for the public sector and may even require the government to subsidize the central bank. We show that this is not the case. Using the monetary general equilibrium model of Berentsen et al. (2014), we show how a central bank that supplies reserves through open market operations can always generate non-negative net income, even when using a floor system to implement the Friedman rule.
Keywords: E42; E52; E58; 330; monetary policy implementation; central bank operations; interest on reserves